2015
DOI: 10.1063/1.4927768
|View full text |Cite
|
Sign up to set email alerts
|

Studies on structural, thermal and AC conductivity scaling of PEO-LiPF6 polymer electrolyte with added ionic liquid [BMIMPF6]

Abstract: Preparation and characterization of polymer electrolyte films of PEO+10wt.% LiPF 6 +xwt.% BMIMPF 6 (1-butyl-3-methylimidazolium hexafluorophosphate) containing dopant salt lithium hexafluorophosphate (LiPF 6 ) and ionic liquid (BMIMPF 6 ) having common anion PF -6 are reported. The ionic conductivity of the polymer electrolyte films has been found to increase with increasing concentration of BMIMPF 6 in PEO+10 wt.% LiPF 6 due to the plasticization effect of ionic liquid. DSC and XRD results show that the cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 62 publications
1
29
0
Order By: Relevance
“…A detailed phase diagram of PEO-based system indicating the melting of crystalline part of PEO and its complex can be seen in the literature. 16,26,34 Similar DSC thermograms have been obtained for other compositions.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…A detailed phase diagram of PEO-based system indicating the melting of crystalline part of PEO and its complex can be seen in the literature. 16,26,34 Similar DSC thermograms have been obtained for other compositions.…”
Section: Resultssupporting
confidence: 76%
“…ILs are considered as promising green electrolytes due to their unique and excellent characteristics such as negligible vapor pressure, nonflammability, noncorrosive with high thermal stability which makes them suitable for applications as electrolytes for energy conversion, storage devices, and suitable as plasticizers. 14 20 Sodium ion–conducting polymer electrolytes based on PEO complexed with sodium hexafluorophosphate , 21 sodium thiocyanate (NaSCN), sodium iodide (NaI), sodium trifluoromethanesulfonate (NaCF 3 SO 3 ), and sodium perchlorate 22 –25 have been reported. The effect of sodium-mixed (NaI, Sodium acetate [NaCH 3 COO], and NaSCN) anion doping in PEO-based polymer electrolytes has been reported by Bhattacharya et al 26 Charge-carrier dynamics in PEO-based polymer electrolytes complexed with NaSCN have been reported by Gupta et al 27 The ionic conductivity of sodium ion–conducting polymer electrolytes based on sodium nitrate (NaNO 3 ) has been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…It is also noted that the value of is greater than unity at lower concentrations of NH 4 NO 3 and low temperature, which suggests the occurrence of the ‘nearly constant loss’ phenomenon in these compositions. Generally, the nearly constant loss behavior in ionic conductors arises from the vibration of ions confined in the asymmetric double-well potential barrier, which correlated to the localized motions of charge carriers between neighboring sites rather than the hopping mechanisms in the conduction processes [ 46 , 47 ]. This phenomenon is observed for low-conducting SPEs at low temperatures, and cannot be observed when there are significant ion dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…Chaurasia et al 153 have also found that upon increasing the IL content in PEs X c decreases. They have also calculated the X c (using Equation 1) which is found to decrease from 83% to 45% upon addition of IL (see Figure 4).…”
Section: Il-based Pes/polymer Gel or Gpe Membranesmentioning
confidence: 89%